E-commerce and export promotion policies for small- and medium-sized enterprises : East Asian and Latin American experiences - Kuwayama, Mikio (ECLAC SantiagoCL, 2001)
Compares the export-orientation of SMEs between Latin America and East Asia and calls for a new approach to SME policy making for Latin America. Contrasts the E-readiness of Latin American countries with that of East Asia. Describes the use of information and communication technology (ICT) by SMEs. Identifies the inhibiting factors for use, and delineates E-commerce potential for SME export promotion. Examines how a range of ICT-enabled business transformations including intranets, extranets, closed and open electronic data interchange (EDI), and other business applications are changing the modes of inter-firm relations of SMEs with transnational companies, large national enterprises and among SMEs themselves.